The determinants of stagflation in a panel of countries - Norbert Berthold; Klaus Gründler (Bayerische Julius-Maximilians-Universität Würzburg, Lehrstuhl für Volkswirtschaftslehre, insbes. Wirtschaftsordnung und Sozialpolitik, 2013)
This paper explores the determinants of stagflation. Three measures are proposed that gauge both the occurrence and the strength of stagflation. We investigate the empirical determinants of these measures, accounting for a range of theoretical hypotheses that have been discussed since the mid-1970s. The results confirm the ambiguity in the influence of oil, although we find clear evidence that adverse supply-shocks enhance the probability and the magnitude of stagflation. However, while stagflation was oil-induced during the 1970s and 1980s, its occurrence in recent decades is strongly affected by monetary policy and labor productivity, indicating a paradigm shift in policy implications. The inevitable policy dilemma, suggested by the empirical persistence of stagflation, may thus be vincible. Yet, while stagflation was more severe during the 1970s and the 1980s, the likelihood of its recurrence turns out to be higher than often thought.
Keywords: E30; O40; 330; Stagflation